Understanding the antecedents of emergency response: A proposed framework - Subramaniam, Chandrakantan; Ali, Hassan; Mohd Shamsudin, Faridahwati (Emerald Group Publishing Limited, 2010)
Purpose – The purpose of this paper is to propose a framework for understanding the antecedents of emergency response performance. Design/methodology/approach – Emergency response is vital in cases of emergencies, as prompt and speedy services determine the difference between life and death.Emergency responders normatively work in team and in concert to ensure that mitigation efforts can be accomplished to reduce loss of life and property. As such, it is imperative that emergency responders perform tasks at hand as efficiently as possible as a team. Findings – The paper discusses possible antecedents that determine an emergency response team’s performance and offers a conceptual framework based on Robbin’s model of group behavior and the existing literature to explain emergency response team performance. Originality/value – The paper presents an overview on emergency management, antecedents of an emergency response team’s performance, and proposes a framework to investigate the antecedents of an emergency response team’s performance.